Status Gizi dan Kelelahan terhadap Produktivitas Kerja - Ajeng Ardhya Ramadhanti (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Workers are one of the factors that influence production, in addition to other factors that support the production process such as skills, time and capital. Workers are the same as the general public who have the right to obtain equality of basic rights, one of which is the right to a healthy life. The diversity of labor nutrition problems is a challenge that must be faced and controlled optimally. The existence of work nutrition is important because the nutritional status will represent the physical quality and immunity of workers, as a component of builders and energy input when the body feels tired due to work, and can increase motivation or enthusiasm for work which will determine work productivity. Research conducted concluded that there is a relationship between nutritional status and fatigue on labor productivity. Therefore optimal regulation of nutritional status by minimizing work fatigue is needed to achieve optimal productivity. Arrangement of working hours, organizing meals, availability of drinking water and sports facilities can be an option to monitor the nutritional status of workers and avoid fatigue as factors that affect productivity.